Recurrent Cranial Bone and Scalp Defect : A Case Report - Hakim, Intan Friscilla; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2012)
Partial defect of the cranial bone and scalp remains a dificult problem for surgeons. Longterm morbidity is due to dif!culty in finding the right material for closure and the resulting repeated surgery. This paper discusses the effectiveness of honey application as a simple and effective method for scalp defect treatment. One case of a patient with partial and cranium defect was referred to Cipto Mangunkusumo hospital with several prior attempt to close the defect with an acrylic implant. The cultured swab on patient revealed MRSA. Application of honey to the raw surface on the cranial defect shows resulting spontaneous epithelialization without clinical evidence of local infection. The use of honey as a topical treatment for cranial and scalp defect provide a safe and effective alternative method for closing the wound secondarily.